Overview of Erythrocyte Indices in Anemia Patients at RSUD Al-Ihsan - Asri, Hanum Julianti; Sudrajat, Agus (Science Tech Group, 2025)
Anemia is a condition characterized by a decrease in the number of erythrocytes and hemoglobin levels in the blood, which can impair physiological function. This study aims to describe the erythrocyte indices in anemia patients treated at RSUD Al-Ihsan Bandung. A descriptive, cross-sectional design was employed, with data obtained from patient medical records. The sample was selected using purposive sampling of patients diagnosed with anemia. The parameters analyzed included erythrocyte count, hemoglobin, hematocrit, MCV, MCH, and MCHC. The results showed significant variations in erythrocyte indices, potentially influenced by demographic and medical history factors. These findings are expected to enhance the understanding of anemia characteristics at RSUD Al-Ihsan and support more effective management and treatment of anemia.